A synergetic linkage between agricultural productivity, nutrition and health (2013)
This study examined the effect of health and nutrition on labour productivity of farmers in South-western Nigeria. Within this geo-political zone of the country, primary data was collected through a field survey of 470 rural farmers. Descriptive statistics, Anthropometric measures of nutrition (BMI and DDS) and the Tobit model were used to show the effect of nutrition and health on the productivity of farmers. Estimated results show that body mass index (BMI) and dietary diversity score (DDS), which are nutritional variables, have effect on the frequency of the occurrence of sickness of rural farmers in the study area; thus affecting their productivity. These results help to establish the synergy between health, nutrition and productivity. Moreover, the policy implication of these findings point to the fact that poor health and malnutrition adversely affect productivity of labour, inversely establishing the fact that good health is a key element of development and a driver of growth. The need arises, therefore, to invest more on human capital, especially health in order to enhance the productive capacity of rural farmers.